Dendrochronological laboratory for studies relate to ENSO events in the tropical zone of South-America - Rodriguez, Rodolfo (1999)
The Collaborative Research Network (CRN) project the assessment of present, past and future climate variability in the Americas from freeline environments, currently under development by institutions of Argentina, Bolivia, Canada, Chile and United State. The goal of this CRN project is the recovery of tree-ring records of past climate from freelines sits along the cordillera between Alaska and Tierra del Fuego. It will be used to reconstruct the major made of interhemispheric climate variability for the past centuries free-ring reconstruction of precipitation and temperature will allow delailed study of local and regional climate variability, how it changes with latitude and is linked to the major elements of ocean and global circulation, through a proposal to the program to expand capacity in the Americas (PESCA) of inter-American Institute for Global change Research (IAI) a very and critical area of South-America has been incorporate to such as studies.